SARS-CoV-2 and Multiple Sclerosis: Potential for Disease Exacerbation - MacDougall, Madison; El-Hajj Sleiman, Jad; Beauchemin, Philippe; Rangachari, Manu (Frontiers in Immunology, 2022)
While the respiratory tract is the primary route of entry for SARS-CoV-2, evidence shows that the virus also impacts the nervous system. Intriguingly, case reports have documented SARS-CoV-2 patients presenting with demyelinating lesions in the brain, spinal cord, and optic nerve, suggesting possible implications in disorders such as multiple sclerosis (MS) and other related neuroimmune disorders. However, the cellular mechanisms underpinning these observations remain poorly defined. The goal of this paper was to review the literature to date regarding possible links between SARS-CoV-2 infection and neuroimmune demyelinating diseases such as MS and its related disorders, with the aim of positing a hypothesis for disease exacerbation. Literature suggests that SARS-CoV, SARS-CoV-2, and orthologous murine coronaviruses invade the CNS via the olfactory bulb, spreading to connected structures via retrograde transport. We hypothesize that a glial inflammatory response may contribute to damaged oligodendrocytes and blood brain barrier (BBB) breakdown, allowing a second route for CNS invasion and lymphocyte infiltration. Potential for molecular mimicry and the stimulation of autoreactive T cells against myelin is also described in the paper. It is imperative that further studies on SARS-CoV-2 neuroinvasion address the adverse effects of the virus on myelin and exacerbation of MS symptoms, as nearly 3 million people suffer from MS worldwide.